Capturing complex perceptions: a case study on consumer responses to brand disclosures about the use of AI in content marketing - Case, Hailey Rose (My University, 2025)
As artificial intelligence (AI) reshapes content marketing, brands are facing increasing scrutiny over transparency, authenticity, and consumer trust. While AI can be efficient, its role in creative storytelling raises concerns about authenticity and its impact on jobs in the creative field. This study examines consumer, media, and industry responses to AI-generated advertising, focusing on the AI-authorship effect, the idea that audiences react differently to AI-created content depending on its context. Using a qualitative case study approach, this research analyzes YouTube comments on AI-generated ads from Dove and Coca-Cola, commentary from televised discussions, and insights from industry professionals. Key themes include concerns about authenticity, AI’s effect on creative jobs, and consumer preferences for human-driven content. The study provides insights into best practices for AI-related brand messaging, emphasizing the importance of aligning AI adoption with audience expectations to maintain trust and prevent reputational risks.
Keywords: Artificial intelligence; Consumer perceptions; Content marketing; Generative AI; AI in marketing